Clinical features and outcomes of prolonged mechanical ventilation: a single-center retrospective observational study - Isao Nagata; Tetsuhiro Takei; Junji Hatakeyama; Masafumi Toh; Hiroyuki Yamada; Michiko Fujisawa (JA Clinical Reports, 2019)
Abstract Background Information on epidemiology of prolonged mechanical ventilation (PMV) patients in the acute care setting in Japan is totally lacking. We aimed to investigate clinical features, impact, and long-term outcomes of PMV patients. Methods This was a retrospective observational study conducted in a tertiary care hospital. Adult patients who were admitted to our intensive care unit (ICU) from April 2009 to March 2014 and required mechanical ventilation (MV) for ≥ 2 days were included. PMV was defined as having MV for ≥ 21 consecutive days. Results Among 1282 MV patients, 93 (7.3%) required PMV, and median duration of MV was 37.0 days. Compared with the non-PMV patients, PMV patients had longer total ICU and high care unit (HCU) stay (34.0 vs. 7.0 days, p < 0.001), longer hospital stay (74.0 vs. 35.0 days, p < 0.001), and higher hospital mortality (54.8 vs. 21.4%, p < 0.001). In multivariable logistic regression analysis, emergency ICU admission and steroid use during MV were associated with PMV. The Kaplan–Meier curves for MV withdrawal and ICU/HCU discharge were almost identical. Among PMV patients, 52 (55.9%) died, 29 (31.2%) were successfully liberated from MV during hospitalization, and 12 (12.9%) still required MV at discharge. Conclusion In this investigation, 7.3% of the patients with MV required PMV. Most PMV patients were liberated from MV during hospitalization, while occupying critical care beds for an extended period. A nationwide survey is required to further elucidate the overall picture of PMV patients and to discuss whether specialized weaning centers to treat PMV patients are required in Japan.